Neoptolemus’ indecision in Sophocles’ Philoctetes. A philosophical reading - Ciruzzi, Luciano (Revista Archai, 2022)
Among the Sophoclean heroes, the figure that stands out is the one of Neoptolemus, in particular because of his difficulty when successfully delivering a course of an action. The young man assumes to carry out a ruse devised by Odysseus in order to obtain the infallible bow of Philoctetes, who has been living for ten years marooned in the deserted island of Lemnos. But once being close to his goal, he is suddenly seized by a doubt that prevents him from achieving such purpose, and therefore undermining his capacity as an agent. Neoptolemus eventually confesses to the lonely islander the dishonest motive for his presence, and, by excusing himself, claims to be governed by a"necessity"(v.923:ananke). This paper will firstly expose the context of development and characteristics of the plan devised by the ingenious king of Ithaca; and will secondly explain Neoptolemus’ indecision based on the particular relationship between his discourse and the reality he pretends; moreover it will emphasize the ontological derivations of the central conflict of the play and, finally, it will enter in to the practical corollaries regarding the previous points.